2007
DOI: 10.1002/nur.20225
|View full text |Cite
|
Sign up to set email alerts
|

Wellness motivation in cardiac rehabilitation: The role of self‐knowledge in cardiovascular risk modification

Abstract: Understanding the factors that motivate behavioral change is central to health promotion efforts. We used qualitative descriptive methods in an effort to understand the role of self-knowledge in the process of risk factor modification. The sample consisted of 17 men and 7 women with diagnosed coronary heart disease, who were attempting to initiate and sustain programs of cardiovascular risk modification. Participants described selfknowledge in terms of three contextually situated patterns: representational, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 64 publications
1
20
0
1
Order By: Relevance
“…And what can we learn to help motivate others? 'Wellness motivation' conceptions of the self are thought to be particularly important (Fleury and Sedikides, 2007). A study into the role of self-knowledge and the modifi cation of cardiovascular risk suggested the following useful framework to consider in future cognitive behavioural programmes: representing the issue (how do I desire myself to be?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And what can we learn to help motivate others? 'Wellness motivation' conceptions of the self are thought to be particularly important (Fleury and Sedikides, 2007). A study into the role of self-knowledge and the modifi cation of cardiovascular risk suggested the following useful framework to consider in future cognitive behavioural programmes: representing the issue (how do I desire myself to be?…”
Section: Discussionmentioning
confidence: 99%
“…What am I afraid of becoming? ), evaluating the issue (creating short-and long-term goals and expectations for behavioural outcomes, gauging my personal effi cacy) and implementing behavioural action (creating behavioural strategies, negotiating the social context and creating self-monitoring strategies) (Fleury and Sedikides, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing interest in non-health related motivations underlying the decision to change eating habits (Fleury, 1996;Fleury & Sedikides, 2007), reflecting a general shift from a strict biomedical perspective, which considers health as the mere absence of disease, to a broader, holistic perspective, which considers health and well-being as equally important components of individual welfare (McMahon & Fleury, 2012). This is the case across the whole lifecycle, including later stages of life.…”
Section: Introductionmentioning
confidence: 97%
“…Si è così passati dai primi studi sul "Tipo A" [4,5,6], all'impatto degli stress psico-sociali [7,8,9,10], allo studio delle relazioni fra depressione e malattia cardiache [11,12,13,14,15], all'identificazione di fattori protettivi quali il supporto psico-sociale [16,17,18], fino a specificare quali modalità di reazione del paziente potessero favorirlo o meno nella gestione di un evento cardiaco quali l'autoefficacia [19,20,21,22] o le modalità di attribuzione causale come il locus of control [23,24,25].…”
unclassified